Effect of environmental pollution on indicators of humoral immunity in patients with neonatal sepsis - Olena Vasylivna Vlasova; Mariana Ivanivna Hrytsiuk (Kazimierz Wielki University, 2020)
The problem of an unfavorable impact of environmental factors on the population's health is becoming significantly important every year and is being actively discussed by leading experts around the world. Therefore, the aim of the study was to determine the indicators of humoral immunity in 260 newborns with neonatal sepsis under different conditions of environmental pollution of their parents' residence. There was a bigger part of prematurely born children among patients with neonatal sepsis living in polluted areas.  The level of immunoglobulins A, M, G in the blood serum of a group of children whose parents lived in polluted areas were established to be significantly lower than in newborns whose parents lived in clean areas. Patients with neonatal sepsis whose parents lived in polluted areas of the city had significantly lower indicators of immunoglobulin levels in blood serum than children whose parents lived in rural areas.